The leverage of “text type” on translation choices: An empirical study with a logical focus - Li, Xueying; Jing, Yi (Meta, 2023)
This article explores the influence of text type on translation choices by attending to the case of logical meaning in Chinese-to-English translation. Drawing on the text typology in Systemic Functional Linguistics, this study analyses four different types of text—expounding, reporting, sharing and recommending. Results show that no shifts and minor shifts occur more frequently in the translation of expounding and reporting texts, whereas major shifts (such as the removal of a logical relation) are more frequently adopted in sharing and recommending texts. These preferences of translation choices can be interpreted in terms of the particularities of different text types, including the explicitness of logical relations, text complexity and text orientation. Thus, the current study can help translators make informed choices when translating texts in different types and enable them to justify their translation choices with reference to linguistic particularities of each text type.